PENGGUNAAN REGRESI MULTIVARIAT UNTUK MENGIDENTIFIKASI PENGARUH LINGKUNGAN KELUARGA TERHADAP MOTIVASI BELAJAR ANAK - Riska Maulia; Rizky Kurniawan; Sabrina Amelia Vega; Osep Hijuzaman (Jurnal Manajemen Pendidikan, 2026)
This research seeks to understand how different family factors, such as the way parents raise their children, the family's economic situation, and how much attention parents give, affect children's motivation to learn, both from within and outside themselves. The study is based on the idea that learning motivation is shaped by multiple elements interacting in the family setting. The research used a quantitative method with a survey design. Information was gathered from students ranging from elementary to high school who live with their parents. The tool for research consisted of a detailed questionnaire measured through a five-point Likert scale. The data analysis involved multivariate regression to explore the effects of parenting style, family economic status, and parental attention on both intrinsic and extrinsic motivations for learning. The results show that parenting style, family economic status, and parental attention positively and significantly impact children's intrinsic and extrinsic motivation to learn. Of the three factors studied, parental attention has the greatest effect on both types of learning motivation. This indicates that being actively involved as a parent is essential for boosting children's desire to learn.